Comparison of Virtual Patient Simulation With Mannequin-Based Simulation for Improving Clinical Performances in Assessing and Managing Clinical Deterioration: Randomized Controlled Trial - Liaw, Sok Ying; Chan, Sally Wai-Chi; Chen, Fun-Gee; Hooi, Shing Chuan; Siau, Chiang (JMIR Publications, 2014)
BackgroundVirtual patient simulation has grown substantially in health care education. A virtual patient simulation was developed as a refresher training course to reinforce nursing clinical performance in assessing and managing deteriorating patients. ObjectiveThe objective of this study was to describe the development of the virtual patient simulation and evaluate its efficacy, by comparing with a conventional mannequin-based simulation, for improving the nursing students' performances in assessing and managing patients with clinical deterioration. MethodsA randomized controlled study was conducted with 57 third-year nursing students who were recruited through email. After a baseline evaluation of all participants' clinical performance in a simulated environment, the experimental group received a 2-hour fully automated virtual patient simulation while the control group received 2-hour facilitator-led mannequin-based simulation training. All participants were then re-tested one day (first posttest) and 2.5 months (second posttest) after the intervention. The participants from the experimental group completed a survey to evaluate their learning experiences with the newly developed virtual patient simulation. ResultsCompared to their baseline scores, both experimental and control groups demonstrated significant improvements (P<.001) in first and second post-test scores. While the experimental group had significantly lower (P<.05) second post-test scores compared with the first post-test scores, no significant difference (P=.94) was found between these two scores for the control group. The scores between groups did not differ significantly over time (P=.17). The virtual patient simulation was rated positively. ConclusionsA virtual patient simulation for a refreshing training course on assessing and managing clinical deterioration was developed. Although the randomized controlled study did not show that the virtual patient simulation was superior to mannequin-based simulation, both simulations have demonstrated to be effective refresher learning strategies for improving nursing students' clinical performance. Given the greater resource requirements of mannequin-based simulation, the virtual patient simulation provides a more promising alternative learning strategy to mitigate the decay of clinical performance over time.